2021
DOI: 10.21203/rs.3.rs-390645/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analytical, Numerical and Experimental Study of an Enhanced Nonlinear Energy Sink

Abstract: Based on theoretical and experimental investigations, this paper proposes a nonlinear energy sink (NES) with piecewise linear springs to enhance vibration suppression effects. A cubic nonlinear oscillator is coupled with a piecewise linear spring to form an enhanced NES (E-NES). Without adding a new resonance region and changing the resonance frequency of the primary system, the enhanced NES can achieve better vibration suppression effects. Based on the free vibration and the forced vibration, the influence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…The empirical formula for the aerodynamic cross-sectional shape of the different columns has a corresponding structure, especially for D-shaped structures, triangular structures, and elliptical structures. The vibration frequency of the gallop-type energy harvesting device is generally low, the flow velocity width is not more than 50 m/s, and the vibration process is mostly nonlinear vibration [37][38][39][40], the vibration amplitude is large, and the structure is prone to overload. From the above research, it is found that the gallop-type energy collection device has a small structure and high energy conversion efficiency.…”
Section: Research Status Analysis Of Galloping Energy Harvesting Devicementioning
confidence: 99%
“…The empirical formula for the aerodynamic cross-sectional shape of the different columns has a corresponding structure, especially for D-shaped structures, triangular structures, and elliptical structures. The vibration frequency of the gallop-type energy harvesting device is generally low, the flow velocity width is not more than 50 m/s, and the vibration process is mostly nonlinear vibration [37][38][39][40], the vibration amplitude is large, and the structure is prone to overload. From the above research, it is found that the gallop-type energy collection device has a small structure and high energy conversion efficiency.…”
Section: Research Status Analysis Of Galloping Energy Harvesting Devicementioning
confidence: 99%